Older Adults and Smart Technology: Facilitators and Barriers to Use - Harris, Maurita T.; Blocker, Kenneth A.; Rogers, Wendy A. (Frontiers in Computer Science, 2022)
Smart technologies (e.g., smartphones, smart security technologies, digital home assistants) have advanced over the years and will continue to do so. There are various benefits to using these technologies in one’s life, such as an increase in productivity through automation and self-monitoring one’s health. Older adults particularly may benefit from smart technologies to support their everyday activities and compensate for age-related changes. In this study, we explored the experiences and attitudes of eighty older adults including those who had prior experience and those who had never used (or perhaps never heard of) smart technologies through an online survey. We assessed their general opinions toward using smart technology and explored what facilitated or hindered their use. Older adults rated the facilitators to use for each smart technology differently, with few commonalities between the order of the most agreed upon facilitators. However, older adults’ opinions were consistent across each technology about their ignorance of technological features and cost of the smart technology, which could be potential barriers to use. Among those who had never used one of the smart technologies, privacy was the most commonly endorsed concern. The results from this study support the understanding of key considerations when developing and deploying smart technologies for older adults.